2011
DOI: 10.1088/0022-3727/44/15/155406
|View full text |Cite
|
Sign up to set email alerts
|

High Seebeck coefficient AMXP2 (A = Ca and Yb; M, X = Zn, Cu and Mn) Zintl phosphides as high-temperature thermoelectric materials

Abstract: Resistivity (ρ), Seebeck coefficient (α) and thermal diffusivity of the title compounds CaZn2P2, YbZn2P2, YbCuZnP2 and YbMnCuP2 are measured over a temperature range 300–1000 K to evaluate the thermoelectric potential of these materials. The temperature dependence of ρ and α of these light weight and less explored Zintl phosphides is similar to that of a degenerate semiconductor. While the electrical transport properties ρ and α are strongly composition dependent, thermal conductivity (κ) calculated from therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…In contrast, compounds with lighter pnictogen atoms such as As and P have been less studied, because thermal conductivity generally increases with lighter atoms. [28,29] Recently, we have found that (Ba,K)Zn 2 As 2 exhibits quite a low value of κ L = 0.8 W/mK at 773 K. This is comparable with Sb-based compounds, leading to a ZT value of 0.67. [30] Although the crystal structure of (Ba,K)Zn 2 As 2 is the α-BaCu 2 S 2 -type [31] different from the CaAl 2 Si 2type, this suggests that As-based compounds can also be promising thermoelectric materials.…”
Section: Introductionmentioning
confidence: 85%
“…In contrast, compounds with lighter pnictogen atoms such as As and P have been less studied, because thermal conductivity generally increases with lighter atoms. [28,29] Recently, we have found that (Ba,K)Zn 2 As 2 exhibits quite a low value of κ L = 0.8 W/mK at 773 K. This is comparable with Sb-based compounds, leading to a ZT value of 0.67. [30] Although the crystal structure of (Ba,K)Zn 2 As 2 is the α-BaCu 2 S 2 -type [31] different from the CaAl 2 Si 2type, this suggests that As-based compounds can also be promising thermoelectric materials.…”
Section: Introductionmentioning
confidence: 85%
“…Property measurements indicate significant changes in the electrical properties, while thermal conductivities for all compositions remain near 1.0 W m –1 K –1 at 673 K. The compositional tuning of ZnCu 2 P 8 to Zn 0.75 Cu 2 P 8 reveals a substantial improvement of zT to 0.25, a more than 150% increase. Although not competitive with well-known thermoelectric materials, compared to the best performing phosphides, Ag 6 Ge 10 P 12 and YbCuZnP 2 , the electrical and thermal transport properties are within comparable values at 673 K, with the added benefit of being composed of earth-abundant elements. ,, Further studies including controlling P content and transport property characterization on other members of this structure type are required to realize the full thermoelectric potential of this family of materials. However, ZnCu 2 P 8 seems to be a reasonable starting template for a less toxic, more cost-effective, tunable thermoelectric material.…”
Section: Discussionmentioning
confidence: 96%
“…Despite being often overlooked in the past, recent computational studies have demonstrated that binary and ternary phosphides can be efficient thermoelectric materials. ,, Not only have they proven to be interesting computationally, but examples such as NiP 2 and REZnCuP 2 (RE = Pr, Nd, Er) have experimentally been shown to match well with computational efforts. , Furthermore, experimentally, there have been promising reports on the phosphides YbCuZnP 2 and Ag 6 Ge 10 P 12 achieving thermoelectric figures of merit, zT , as high as 0.6 and 0.7, respectively. , …”
Section: Introductionmentioning
confidence: 99%
“…Various thermoelectric materials have been investigated for the past several decades. Among them, Zintl compounds, which consist of covalently bonded anionic frameworks and cations, have been studied extensively because of their fascinating compositional/structural varieties and promising thermoelectric properties. For example, AB 2 X 2 , A 14 BX 11 , A 3 BX 3 , A 5 B 2 X 6 , A 9 B 4+ δ X 9 , and A 2 BX 2 where A denotes an alkali/alkaline-earth/rare-earth metal, B is a (post-)­transition metal, and X is a pnictogenhave been demonstrated as promising thermoelectric materials. In particular, Mg 3 (Sb,Bi) 2 which is also categorized as an AB 2 X 2 system because the Mg atoms are located at two crystallographic sitesexhibits ZT = 1.51 at 716 K. , So far, most studies of Zintl thermoelectric compounds have employed Sb as the constituent pnictogen X, while investigations that employ lighter pnictogens such as As and P are still sporadic and not firmly established. , However, recent studies have demonstrated that As-based Zintl compounds, including (Ba, K)­Zn 2 As 2 and (Ba, K)­Cd 2 As 2 , can also show promising thermoelectric properties. Furthermore, n-type polarity was unexpectedly observed in Eu 3 InAs 3 . Although the use of arsenides is not straightforward for practical applications, expanding the frontier for efficient thermoelectric materials may provide a new paradigm for developing next-generation energy materials, as exemplified by iron–arsenide superconductors with high transition temperatures…”
Section: Introductionmentioning
confidence: 99%